Peran Badan Permusyawaratan Desa (BPD) Dalam Proses Demokratisasi Desa Tapenpah Kecamatan Insana Kabupaten Timor Tengah Utara - Neonbeni, Randy Vallentino; Talan, Rudobertus (Universitas Gajah Putih, 2022)
This research was conducted in Tapenpah Village, Insana District, TTU Regency. To achieve this goal, the authors use data collection techniques in the form of library research and field research by conducting direct interviews with resource persons. The results showed that the implementation of the Village Head election in Tapenpah Village starting from the preparation, nomination, voting, and determination stages was carried out safely, orderly and in accordance with North Central Timor Regency Regional Regulation Number 4 of 2019 concerning Procedures for Election and Dismissal of Village Heads. In addition, from the results of the study, the authors also found things that were inhibiting the implementation of the Tapenpah Village head election. The inhibiting factors for simultaneous village head elections in Tapenpah Village include the placement of voting that is not strategic, there are still many community members who do not use their voting rights even though they meet the requirements as voters and are elected as voters, rarely socialize about village head elections.